Investigation of the Springback Behaviour of High-strength Aluminium Alloys Based on Cross Profile Deep Drawing Tests - Hetz, Peter; Suttner, Sebastian; Merklein, Marion (Procedia Manufacturing, 2020)
The prediction of springback of sheet metal parts is still a challenge in metal forming processes. To meet the requirements for dimensional accuracy of a sheet metal part, the springback must be compensated and the production process has to be designed accordingly. During forming, elastic energy is stored in the semi-finished product. When removing a part from the deep-drawing tool, the resulting residual stresses with an elastic component cause unwanted changes of the part`s geometry in forming. Especially sheet materials with low elastic modulus and high yield strength tend to an increased springback. Among others, these materials include aluminium alloys of the 7000 series. For this reason, a fundamental understanding of the material behaviour of these materials is relevant for designing a sheet metal forming process. This contribution uses a novel approach to investigate the springback behaviour of AA7020-T6 and AA7075-T6. For this purpose, cross profiles are deep-drawn with various parameter settings and subsequently digitised with a three-dimensional optical measurement system. By analysing the digitised profiles, the springback behaviour is quantified depending on the experimental parameters. Due to the right-angled structure of the cross profile, the influence of anisotropy in 0 and 90 degree to rolling direction is investigated within one forming operation.
CRIS-Team Scopus Importer:2020-06-05
Keywords: Cross profile; Deep drawing; High-strength aluminium alloys; Springback compensation